Efektivitas Terapi Dzikir Sholawat terhadap Tingkat Kecemasan pada Pasien Pre Sectio Caesarea - Isni Rahim Paramaasri; Wahyu Endang Setyowati; Dwi Heppy Rochmawati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Anxiety is an emotional response that is commonly experienced by patients before surgery, including in pre sectio caesarean patients. High levels of anxiety can affect the patient's physiological and psychological condition, so appropriate handling efforts are needed. Non-pharmacological interventions, such as prayer dhikr therapy, can be used as an alternative to help reduce anxiety because it provides relaxation, calmness, and increased spirituality. This study aims to analyze the effectiveness of dhikr sholawat therapy on anxiety levels in pre sectio caesarean patients. The research design used a quasi-experiment with a pre-test and post-test control group approach. The research sample consisted of pre-sectio caesarea patients who met the inclusion criteria, then divided into two groups, namely the intervention group that was given prayer dhikr therapy and the control group that only received standard treatment. The instrument used to measure anxiety levels is the Hamilton Anxiety Rating Scale (HARS). Data analysis was carried out by statistical tests according to the distribution of data to find out the difference in results between the two groups. The results showed a significant decrease in anxiety levels in the intervention group compared to the control group (p < 0.05). These findings prove that prayer dhikr therapy is effective in reducing anxiety in pre-sectio caesarean patients. Thus, this therapy can be recommended as one of the non-pharmacological nursing interventions that support the improvement of service quality and patient comfort.